Pemberdayaan Ekonomi Masyarakat Berbasis Teknologi Bioflok Pada Kelompok Usaha Tani di Kelurahan Tarus Kabupaten Kupang - Jasron, Jahirwan Ut; Turupadang, Welem Linggi; Magesa, Daud Pulo (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
The Community Partnership Empowerment program entitled Community Economic Empowerment Based on Biofloc Technology with Green Energy in Farmer Business Groups in Tarus Village, Kupang Regency, was carried out in Kupang Regency in the Manikin Farmer Business Group chaired by Mr. Frengki Foes. Based on field observations and information obtained from farmer partners, the problems of farmers are problems with knowledge about biofloc technology and problems with fisheries' business management, ranging from business organizations to unclear fisheries' business management. Therefore, this activity provides a solution for empowering farmer groups to become productive entrepreneurs. This PKM has a short-term program: 1) Optimizing unproductive home yard land; 2) Increasing knowledge and skills in tilapia cultivation. This PKM program is implemented for 8 (eight) months with 1 (one) PKM partner. The stages of implementing this PKM include the preparation stage for surveys and site reviews, analysis of potential and partner problems, and implementation of PKM activities. The technology applied in this activity is Biofloc technology in tilapia cultivation in round tarpaulin ponds. Biofloc technology in cultivation minimizes the use of artificial feed and is also efficient in water use. The results of the implementation of this PKM produced 2 (two) units of Biofloc tilapia cultivation ponds and increased community knowledge and skills, especially in the Manikin farming group. To determine the success of this PKM, an evaluation was carried out using a comparative causal quantitative method, namely comparing the level of partner understanding of the mastery of biofloc technology, aeration systems, and feed management before and after the activity. The best improvement was in the level of understanding of fish feed management, while assistance was still needed in the other two areas.